The Effect of Mourino's Narcissism on A Football Club - Soong, S.W.H. (2019)
This study investigates the effects of narcissism on an organisation and also the relationship between narcissism and internal turbulence in the workplace. This study is all done in the context of football management by using case study methods. A case study on José Mourinho was performed to determine how his narcissistic behaviour, if at all, affects the football clubs he manages. From there, the relationship between narcissism and internal turbulence was also discussed. The results found that Mourinho’s narcissism had both negative and positive effects on a football club. The manager’s narcissistic traits were found to cause players to also adopt narcissistic behaviours. Furthermore, his narcissistic behaviour had caused players that did not agree with his philosophy to be neglected and mistreated. On the other hand, Mourinho’s narcissism and hunger for success has proved to be motivational for players to achieve success. The relationship between narcissism and internal turbulence was also investigated. The results support the view that narcissistic behaviour causes internal turbulence in an organisation. However, internal turbulence was also proven to be caused by other factors which provide motivation for further research.